Synthesis, crystal structures and reactivity towards dioxygen of copper(I) complexes with tripodal aliphatic amine ligands. (1st October 2019) - Will, Janine; Würtele, Christian; Becker, Jonathan; Walter, Olaf; Schindler, Siegfried
Graphical abstract: Low temperature stopped-flow investigation on the formation of three mononuclear copper end-on superoxido complexes [(R 1 3 R 2 3 tren)Cu(O2 )] + complex with tripodal ligands of the tren type(R 1  = H, R 2  = CH3 ; R 1  = H, R 2  = isoprop; R 1  = CH3, R 2  = isoprop). Abstract: Copper(I) complexes of the tripodal, tetradentate, aliphatic ligands Me3 tren (Me3 tren = tris-(2-methylaminoethyl)amine), Isoprop3 tren (Isoprop3 tren = tris-(2-isopropylaminoethyl)amine) and Me3 isoprop3 tren (Me3 isoprop3 tren = tris-(2-isopropylmethylaminoethyl)amine) of the Tren-family (Tren = tris(2-aminoethyl)amine) were prepared and structurally characterized. Furthermore, they were reacted in solution at low temperatures with dioxygen. All complexes formed a short-lived superoxido intermediate complex that could be observed using low temperature stopped-flow techniques prior to consecutive reactions. However, the superoxido complexes were too reactive to allow isolation and full characterization in contrast to previous work.